The Effectiveness of A Combination of Mindfulness Meditation and Spiritual Care in Lowering Blood Pressure in Hypertension Patients - Muhammad Farhan Al Farisi; Mesya Mesya; Afif Ghariza; Usman Stiawan (Indonesian Journal of Global Health Research, 2025)
Hypertension is a global health problem known as a silent killer because it often presents without symptoms but can lead to serious complications such as stroke, kidney failure, and heart attack. In Pringsewu Regency, hypertension cases have continued to increase from 2021 to 2023, yet the coverage of healthcare services remains low. Non-pharmacological approaches such as mindfulness meditation and spiritual care have been proven to reduce blood pressure and improve the quality of life for individuals with hypertension. Objective to determine the effectiveness of a combination of mindfulness meditation and spiritual care in lowering blood pressure among individuals with hypertension in Pringsewu Regency. This study used a one-group pretest-posttest design. A total of 100 respondents were selected using purposive sampling based on the inclusion criteria. The intervention, consisting of a combination of mindfulness meditation and spiritual care, was administered during the period of June up to July 2025. Blood pressure was measured before and after the intervention and analyzed using the Paired Samples T-Test. The majority of respondents were female (55%), aged 36–55 years (44%). In terms of smoking history, most respondents were non-smokers (61%), and based on family history, most did not have a family history of hypertension (59%). The results of the Paired Samples T-Test showed a p-value = 0.000 (p ≤ 0.05), indicating a significant difference in blood pressure before and after the intervention. The combination of mindfulness meditation and spiritual care is effective in lowering blood pressure among individuals with hypertension in Pringsewu Regency.